Age-related differences in pelvic and trunk motion and gait adaptability at different walking speeds. Issue 5 (October 2015) - Gimmon, Yoav; Riemer, Raziel; Rashed, Hisham; Shapiro, Amir; Debi, Ronen; Kurz, Ilan; Melzer, Itshak
Abstract This study aimed at investigating age-related changes in gait kinematics and in kinematic adaptations over a wide range of walking velocities. Thirty-four older adults and 14 younger adults walked on a treadmill; the treadmill velocity was gradually increased in increments of 0.2 miles/hour (mph) (1.1–1.9 mph) and then decreased in the same increments. Pelvic, trunk, upper limbs and lower limbs angular total ranges of motion (tROM), stride time, stride length, and step width were measured. The older adults had lower pelvic, trunk tROM and shorter strides and stride time compared with the younger adults. As the treadmill speed was gradually increased, the older adults showed an inability to change the pelvic list angular motions (3.1 ± 1.3° to 3.2 ± 1.4°) between different walking velocities, while the younger adults showed changes (5.1 ± 1.8° to 6.3 ± 1.7°) as a function of the walking velocity. As the walking velocity increased, the older adults increased their stride length (from 57.0 ± 10 cm to 90.2 ± 0.1 cm) yet stride times remained constant (from 1.17 ± 0.3 sec to 1.08 ± 0.1 sec), while the younger adults increased stride length and reduced stride times (from 71.4 ± 10 cm to 103.0 ± 7.9 m and from 1.45 ± 0.2 sec to 1.22 ± 0.1 sec, respectively). In conclusion, the older adults were unable to make adaptations in pelvic and trunk kinematics between different walking speeds (rigid behavior), while the younger adults showed more flexible behavior. Pelvic and trunk kinematics in different walking speeds can be used as variables in the assessment of gait in older adults.